2018
DOI: 10.1167/iovs.18-25039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Uveitis on the Development of Keratopathy: A Population-Based Cohort Study

Abstract: The purpose of this study was to evaluate the effect of uveitis on the development of various keratopathies via the use of the National Health Insurance Research Database (NHIRD) in Taiwan. METHODS. Approximately 1 million patients were randomly sampled from the registry of the NHIRD. Patients diagnosed with uveitis by ophthalmologists were enrolled in the study group after exclusion. Each individual in the study group was age and sex matched to four nonuveitis individuals who serve as the control group. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…The mean age and sex of patients with uveitis in this study are compatible with those in another population-based study conducted in Taiwan [ 26 ]. In addition, we found that hypertension, diabetes, hyperlipidaemia and obesity were significantly more prevalent in patients with uveitis than in the non-uveitis group.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The mean age and sex of patients with uveitis in this study are compatible with those in another population-based study conducted in Taiwan [ 26 ]. In addition, we found that hypertension, diabetes, hyperlipidaemia and obesity were significantly more prevalent in patients with uveitis than in the non-uveitis group.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, we found that hypertension, diabetes, hyperlipidaemia and obesity were significantly more prevalent in patients with uveitis than in the non-uveitis group. Previous studies also have revealed associations between uveitis and these comorbidities [26,27]. Since hypertension, diabetes, hyperlipidaemia and obesity are also risk factors for cardiovascular diseases, uveitis patients may have a higher possibility for developing cardiovascular diseases.…”
Section: Plos Onementioning
confidence: 97%
“…Ocular surface disease is an important yet mostly neglected perspective in taking care of BD patients with ocular involvement [8]. Population-based study found an increasing risk of keratopathy in uveitic patients [9]. Studies revealed that a significant decrease of tear break-up time and goblet cell counts, as well as increased squamous conjunctival metaplasia in ocular BD [10,11].…”
mentioning
confidence: 99%